Risk Factors for Functional Outcomes in Advanced Laryngeal Squamous Cell Carcinoma. (25th May 2022) - Lee, David S.; Lee, Jake J.; Sinha, Parul; Puram, Sidharth V.; Jackson, Ryan S.; Adkins, Douglas R.; Oppelt, Peter; Brenneman, Randall; Thorstad, Wade L.; Pipkorn, Patrik
Abstract : Objective: Chemoradiation for patients with laryngeal squamous cell carcinoma (SCC) may achieve organ preservation, but appropriate patient selection remains unknown. This study investigates pre‐treatment risk factors associated with functional and survival outcomes after radiation‐based therapy in patients with advanced laryngeal SCC. Methods: A retrospective cohort study was performed on 75 adult patients with stage III or IV laryngeal SCC receiving definitive radiation‐based therapy from 1997 to 2016 at a tertiary care center. Tracheostomy and gastrostomy dependence were the primary functional outcomes. Multivariable logistic regressions were performed to evaluate relationships between pre‐treatment factors and tracheostomy and gastrostomy dependence. Time‐to‐event analyses were performed to determine risk factors associated with overall survival. Results: Among 75 patients included in the analysis, 30 (40%) patients were tracheostomy dependent and 31 (41%) were gastrostomy tube dependent. The median length of follow‐up was 31 months (range = 1 to 142 months). Pre‐treatment tracheostomy was a significant predictor of post‐treatment tracheostomy (aOR = 13.9, 95% CI = 3.35 to 57.5) and moderate–severe comorbidity was a significant predictor of post‐treatment gastrostomy dependence (aOR = 2.96, 95% CI = 1.04 to 8.43). The five‐year overall survival was 51% (95% CI = 38 to 64%). Pre‐treatment gastrostomy tube dependence was associated with an increased risk of death (aHR = 2.45, 95% CI = 1.09 to 5.53). Conclusions: Baseline laryngeal functional status and overall health in advanced laryngeal SCC are associated with poor functional outcomes after radiation‐based therapy, highlighting the importance of patient selection when deciding between surgical and non‐surgical treatment plans. Laryngoscope, 133:594–600, 2023 Abstract : This study investigates pre‐treatment risk factors associated with functional and survival outcomes after radiation‐based therapy in patients with advanced laryngeal squamous cell carcinoma (SCC). When controlling for confounding variables, baseline laryngeal functional status and overall health in advanced laryngeal SCC are associated with poor functional outcomes after radiation‐based therapy. These findings highlight the importance of patient selection when deciding between surgical and non‐surgical treatment plans.